PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPETENSI TERHADAP MOTIVASI DAN KINERJA APARATUR PENGAWAS INTERN PEMERINTAH (APIP) PADA INSPEKTORAT PROVINSI RIAU - Abdillah, Rhomas; Hendriani, Susi (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to analyze the influence transformational leadership andcompetence toward motivation and work performance of government internalsupervisor (GIS â APIP) of Inspektorat Provinsi Riau. The background of the study isthat the work performance of government internal supervisor is (so far) very low. Thismatter needs a solution in order to increase the work performance quality to the level ofgood or effective in commencing his/her functions.The data of the study consist ofprimary and secondary data from 111 civil servants as the population and sample aswell (total sample). The needed data were collected through questionnaire andinterview. The collected data were analyzed by using descriptive analysis andquantitative analysis to test the hypothesis by applying PLS (Partial Least SquareVersion 3). The findings of the research are as the following: (1) there is a significantinfluence between transformational leadership and work performance of governmentinternal supervisor (GIS â APIP), (2) there is a significant influence betweencompetence and work performance of government internal supervisor (GIS â APIP), (3)there is positive influence but not significant between transformational leadershiptoward motivation (as an interviewing variable), (4) there is a positive influence but notsignificant between competence and work performance through motivation, (5) there isa positive influence but not significant between motivation and work performance ofgovernment internal supervisor (GIS â APIP)